Multi-wavelength high-polarization-degree straight-cavity surface emitting laser
By designing a periodically cyclic arithmetic sequence strip waveguide structure in the upper waveguide layer of a straight cavity surface emitting laser with high polarization degree, the problems of difficult and cost of manufacturing multi-wavelength lasers in the prior art are solved, and an efficient and economical multi-wavelength emission effect is achieved.
Patent Information
- Application Number
- CN202510304505.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-14
- Publication Date
- 2025-06-10
AI Technical Summary
The existing multi-wavelength vertical cavity surface emission lasers are difficult to manufacture and costly, making it difficult to achieve efficient emission of multiple wavelengths in a single device.
A straight cavity surface emission laser with multiple wavelengths and high polarization is designed, and the upper waveguide layer consists of a plurality of bar waveguides of different widths and fill materials arranged parallelly in the same plane. The width of the bar waveguide changes into a periodic cyclic arithmetic sequence.
Through the special design of the upper waveguide layer, complex sub-wavelength grating etching process is avoided, manufacturing process is simplified and costs are reduced, while improving production flexibility and controllability.
Smart Images

Figure CN120127499A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of semiconductor technology, and particularly to a straight cavity surface emitting laser with multi-wavelength and high polarization degree. Background Art
[0002] The fabrication of multi-wavelength vertical cavity surface emitting lasers (VCSELs) usually faces many challenges, mainly due to its complex design and structural requirements. Compared with single-wavelength VCSELs, multi-wavelength VCSELs need to achieve efficient emission of multiple wavelengths simultaneously in a single device, which significantly increases the manufacturing difficulty. Conventional fabrication methods often struggle to meet such complex requirements.
[0003] The most commonly used method is to obtain VCSELs by etching sub-wavelength gratings with different periods. Sub-wavelength gratings are micro-nano structures whose periods and shapes can precisely control the optical properties of different regions, thereby achieving emission of different wavelengths. However, although this method can effectively obtain VCSELs, it faces huge technical challenges and high production costs.
[0004] Therefore, how to reduce the technical difficulty and production cost involved in VCSEL fabrication while ensuring efficient emission has become a problem to be solved. Summary of the Invention
[0005] Based on the above problems, the present application provides a straight cavity surface emitting laser with multi-wavelength and high polarization degree, which can provide a highly reliable laser structure for wide bandgap semiconductor devices with a sandwich epitaxial structure.
[0006] The embodiments of the present application disclose the following technical solutions:
[0007] A straight cavity surface emitting laser with multi-wavelength and high polarization degree, the laser comprising a lower electrode layer, a substrate layer, a lower distributed Bragg reflector (DBR) layer, a lower spacer layer, a lower waveguide layer, a quantum well layer, an upper waveguide layer, an upper spacer layer, an upper DBR layer, and an upper electrode layer stacked in sequence;
[0008] The upper waveguide layer includes a plurality of strip waveguides with different widths arranged in parallel in the same plane, and a filling material filled between the plurality of strip waveguides; the widths of the plurality of strip waveguides change in an arithmetic progression with a periodic cycle.
[0009] In a possible implementation, the material of the upper waveguide layer has an unintentional doping concentration less than 2×10 17Indium gallium arsenide phosphide (InGaAsP) or aluminum gallium indium arsenide (AlGaInAs) per cubic centimeter; the thickness of the upper waveguide layer is 200 - 400 nanometers; the widths of each strip waveguide in the upper waveguide layer are different, the width of each strip waveguide is 2 - 10 micrometers, and the strip waveguides in the upper waveguide layer form a periodic distribution according to the width change of an arithmetic progression; the filling material is aluminum gallium arsenide (AlGaAs) with a refractive index equal to 2.9.
[0010] In a possible implementation, the lower electrode layer includes a stacked gold germanium nickel layer and a first gold layer; the gold germanium nickel layer is located on the side where the lower electrode layer contacts the substrate layer;
[0011] Among them, the thickness of the gold germanium nickel layer is 40 - 60 nanometers; the thickness of the first gold layer is at least 2000 nanometers; the gold germanium nickel layer and the first gold layer are formed by a magnetron sputtering process.
[0012] In a possible implementation, the lower DBR layer contains 30 to 40 pairs of aluminum gallium arsenide alloy reflection layers;
[0013] Among them, the material of the aluminum gallium arsenide alloy reflection layer includes an aluminum gallium arsenide alloy with 10% aluminum, or an aluminum gallium arsenide alloy with 90% aluminum; the optical thickness of each layer of the aluminum gallium arsenide alloy reflection layer is equal to one - quarter of the lasing wavelength of the laser; both sub - layers in each pair of the aluminum gallium arsenide alloy reflection layers have a composition gradient characteristic; in the lower DBR layer, among the materials of the two layers of aluminum gallium arsenide alloy reflection layers close to the quantum well layer, the N - type doping concentration is less than or equal to 4X10 17 Per cubic centimeter, the N - type doping concentration of the materials of the other aluminum gallium arsenide alloy reflection layers in the lower DBR layer is 4X10 17 -2X10 18 Per cubic centimeter.
[0014] In a possible implementation, the material of the lower spacer layer is InGaAsP or AlGaInAs with an unintentional doping concentration less than 1×10 18 Per cubic centimeter;
[0015] Among them, the thickness of the lower spacer layer is 200 - 400 nanometers; the refractive index of the lower spacer layer is 3.3.
[0016] In a possible implementation, the material of the lower waveguide layer is InGaAsP or AlGaInAs, with a thickness of 200 - 300 nanometers and an unintentional doping concentration less than 2×10 17 Per cubic centimeter.
[0017] In a possible implementation, the material of the lower quantum well layer is with an unintentional doping concentration less than 1×1017 InGaAs or AlGaAs per cubic centimeter;
[0018] Wherein, the thickness of the lower quantum well layer is 20 - 100 nanometers; the lower quantum well layer includes 1 - 5 sub - quantum wells, and each sub - quantum well includes a well layer and a barrier layer; the thickness of the well layer is 4 - 8 nanometers; the thickness of the barrier layer is 6 - 10 nanometers.
[0019] In a possible implementation, the material of the upper spacer layer has a doping concentration less than 1×10 18 AlGaAs per cubic centimeter; the thickness of the upper spacer layer is 200 - 400 nanometers; the refractive index of the upper spacer layer is 2.9.
[0020] In a possible implementation, the upper DBR layer includes a plurality of alloy reflection layers; each alloy reflection layer includes 18 to 24 pairs of aluminum gallium arsenide alloy reflection layers;
[0021] Wherein, the material of the aluminum gallium arsenide alloy reflection layer includes an aluminum gallium arsenide alloy with 10% aluminum or an aluminum gallium arsenide alloy with 90% aluminum; the optical thickness of each layer of the aluminum gallium arsenide alloy reflection layer is equal to one - quarter of the lasing wavelength of the laser; the two sub - layers of each pair of the aluminum gallium arsenide alloy reflection layers both have a compositional gradient characteristic; the P - doping concentration of the material of the two pairs of aluminum gallium arsenide alloy reflection layers adjacent to the active region in the upper DBR layer is not greater than 4X10 17 per cubic centimeter, and the P - doping concentration of the material of the other pairs of aluminum gallium arsenide alloy reflection layers in the upper DBR layer is 4X10 17 -2X10 18 per cubic centimeter;
[0022] The upper DBR layer further includes a high - aluminum layer, and the high - aluminum layer is located on the side where the upper DBR layer contacts the upper spacer layer; a highly doped contact layer is provided at the top of the upper DBR layer, and the thickness of the highly doped contact layer is 20 nanometers; the alloy reflection layers are a plurality of cylinders arranged parallel to the direction of the strip waveguide, and in a cross - section parallel to the extending direction of the upper spacer layer, it is an ellipse with a major axis parallel to the strip waveguide; silicon oxide and / or silicon nitride are filled between the plurality of cylinders.
[0023] In a possible implementation, the upper electrode layer includes a titanium layer and a second gold layer;
[0024] Wherein, the thickness of the titanium layer is 50 - 100 nanometers; the thickness of the second gold layer is at least 300 nanometers.
[0025] Compared with the prior art, the present application has the following beneficial effects:
[0026] The embodiment of the present application provides a vertical cavity surface emitting laser with multiple wavelengths and high polarization degree. The structure of the laser includes a lower electrode layer, a substrate layer, a lower distributed Bragg reflector (DBR) layer, a lower spacer layer, a lower waveguide layer, a quantum well layer, an upper waveguide layer, an upper spacer layer, an upper DBR layer, and an upper electrode layer, which are connected in sequence. Among them, the upper waveguide layer includes a plurality of strip waveguides with different widths arranged in parallel in the same plane, and a filling material filled between the plurality of strip waveguides. The widths of the plurality of strip waveguides change in an arithmetic progression with a periodic cycle. Compared with the conventional method of achieving multi-wavelength emission by etching sub-wavelength gratings with different periods, the present application controls the growth rate difference of the waveguide layer through the special design of the upper waveguide layer (such as the distribution of strip waveguides with different widths), thereby avoiding the complex grating etching process. This not only simplifies the manufacturing process but also reduces the high cost brought by grating etching. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the technical solutions in the embodiments of the present application or the prior art, the following will briefly introduce the drawings required for the description of the embodiments or the prior art. Obviously, the drawings in the following description are only some embodiments of the present application. For those of ordinary skill in the art, without creative efforts, other drawings can be obtained based on these drawings.
[0028] Figure 1 Schematic diagram of a vertical cavity surface emitting laser with multiple wavelengths and high polarization degree provided by an embodiment of the present application;
[0029] Figure 2 Top view schematic diagram of another vertical cavity surface emitting laser with multiple wavelengths and high polarization degree provided by an embodiment of the present application. DETAILED DESCRIPTION OF THE EMBODIMENTS
[0030] A vertical cavity surface emitting laser with multiple wavelengths and high polarization degree provided by the present application can be used in the semiconductor field. The above is only an example and does not limit the application field of the vertical cavity surface emitting laser with multiple wavelengths and high polarization degree provided by the present application.
[0031] Terms such as "first", "second", "third", and "fourth" in the description, claims, and drawings of the present application are used to distinguish different objects, rather than to limit a specific order.
[0032] In the embodiments of the present application, words such as "as an example" or "for example" are used to represent examples, illustrations, or explanations. Any embodiment or design solution described as "as an example" or "for example" in the embodiments of the present application should not be construed as being more preferred or having more advantages than other embodiments or design solutions. Rather, the use of words such as "as an example" or "for example" is intended to present relevant concepts in a specific manner.
[0033] The terms used in the embodiments section of the present application are only used to explain the specific embodiments of the present application and are not intended to limit the present application.
[0034] To facilitate the understanding of the technical solutions provided in the embodiments of the present application, the background technology related to the embodiments of the present application will be described first below.
[0035] VCSELs are usually very difficult to fabricate by conventional methods because they require multiple different wavelength laser outputs to be achieved on the same chip. To achieve this goal, the most commonly used method is to adjust the reflection spectrum of the laser by etching sub-wavelength gratings with different periods, thereby achieving different wavelength outputs. However, this fabrication method requires extremely high precision because the period variation of the grating directly determines the wavelength of the laser. To achieve sub-wavelength level precision, high-precision equipment and technologies are required in the fabrication process, which results in a significant increase in the fabrication cost.
[0036] Specifically, etching sub-wavelength gratings with different periods requires extremely precise process technologies, including steps such as high-precision lithography, etching, and thin film deposition. These steps not only require extremely high process precision but also highly complex equipment and strict process control. In addition, each operation requires highly specialized technical personnel to monitor and adjust to ensure the performance and consistency of the final product. Therefore, the entire manufacturing process is not only time-consuming but also costly. In addition to the technical difficulties, this high-precision manufacturing process also has high requirements for production equipment and maintenance, resulting in material waste and low production efficiency. For example, interlayer alignment errors and surface roughness problems are likely to occur during the lithography and etching processes, and these problems will directly affect the optical performance and stability of the device. Therefore, although etching sub-wavelength gratings is an effective method, its high cost and complexity have limited the application of this technology.
[0037] To solve this problem, an edge-emitting laser with multi-wavelength and high polarization degree is provided in an embodiment of the present application. The structure of the laser consists of multiple layers connected in sequence, including a lower electrode layer, a substrate layer, a lower DBR layer, a lower spacer layer, a lower waveguide layer, a quantum well layer, an upper waveguide layer, an upper spacer layer, an upper DBR layer, and an upper electrode layer. Among them, the upper waveguide layer includes multiple strip waveguides with different widths arranged in parallel in the same plane, and a filling material filled between the multiple strip waveguides. The widths of the multiple strip waveguides change in an arithmetic progression with a periodic cycle. Through the special patterned structure of the upper waveguide layer of the material in the present application, the growth rate difference is realized, thereby controlling the difference in the thickness of the spacer layer, and further affecting the lasing wavelength. This innovative design makes the manufacturing of multi-wavelength and high-polarization-degree array edge-emitting lasers more efficient and economical, and also improves the flexibility and controllability of production. This method avoids the high costs and technical challenges brought by using sub-wavelength gratings in traditional preparation methods, bringing new possibilities and development opportunities for the production of multi-wavelength lasers.
[0038] To enable those skilled in the art to better understand the solution of the present application, the technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present application. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those of ordinary skill in the art without creative efforts shall fall within the protection scope of the present application.
[0039] See Figure 1 , which is a schematic diagram of an edge-emitting laser with multi-wavelength and high polarization degree provided in an embodiment of the present application. The structure of the laser includes a lower electrode layer 1, a substrate layer 2, a lower DBR layer 3, a lower spacer layer 4, a lower waveguide layer 5, a quantum well layer 6, an upper waveguide layer 7, an upper spacer layer 8, an upper DBR layer 9, and an upper electrode layer 10 connected in sequence.
[0040] The design of the upper waveguide layer 7 is crucial for the performance of the laser. The following is a detailed description of the layer structure:
[0041] (1) Material selection: The material of the upper waveguide layer 7 can be indium gallium arsenide phosphide (InGaAsP) or aluminum gallium indium arsenide (AlGaInAs) with an unintentional doping concentration less than 2×10 17 per cubic centimeter. These materials have appropriate band gaps and refractive indices and can be used to adjust the wavelength and resonance characteristics of the laser.
[0042] (2) Thickness range: The thickness range of the upper waveguide layer 7 is 200 - 400 nanometers. Such a thickness can ensure the functional effectiveness of the upper waveguide layer 7 and adapt to different laser design requirements.
[0043] (3) Design of the filling material: In the upper waveguide layer 7, multiple filling materials ( Figure 1 In Figure 1 , the white shaded part in the upper waveguide layer 7 is the filling material) are evenly distributed. These filling materials start to fill from one end of the upper waveguide layer ( Figure 1 In Figure 1 , the filling material starts to fill from the rightmost end of the upper waveguide layer 7).
[0044] (4) Periodic distribution and wavelength adjustment: The widths of these strip waveguides change according to a certain rule, and their different widths cause differences in the local optical properties of the waveguide layer. Through this periodic distribution, the resonant wavelength of the laser can be effectively adjusted. For example, the width difference will cause changes in the thickness of the spacer layer, which in turn affects the resonant conditions, thereby adjusting the emission wavelength of the laser. The width of the strip waveguide is between 2 - 10 microns, and the widths of each strip waveguide are different, and the strip waveguides are arranged according to the width change of an arithmetic progression, so as to achieve the purpose of adjusting the lasing wavelength. The specific difference and quantity are determined by the emission wavelength requirements of the laser.
[0045] (5) Filling material and refractive index: Between these strip waveguides, aluminum gallium arsenide (AlGaAs) material with a refractive index of 2.9 is used for filling. The selection of this material not only ensures the effectiveness of the optical waveguide, but also can control the wavelength and polarization characteristics of the laser. The AlGaAs material acts as an effective refractive index regulator in this structure, enabling the design of the laser to meet the requirements of high polarization selectivity and precise wavelength control.
[0046] (6) High polarization selectivity: An important advantage of the upper waveguide layer 7 is its high polarization selectivity. Since the different widths of the strip waveguides will cause changes in the local refractive index, this non-uniformity enhances the selectivity of the laser for different polarization modes, thereby improving the polarization control and the stability of the laser output.
[0047] This design of the upper waveguide layer 7, through the optimization and adjustment of the periodic structure, can not only improve the performance of the laser (such as wavelength adjustment and polarization selectivity), but also avoid the use of expensive grating structures, improving the economy and flexibility of production. This design makes the manufacturing of multi-wavelength, high-polarization-selectivity array surface-emitting lasers more efficient, promoting new developments in laser technology.
[0048] In a possible implementation, the lower electrode layer 1 is composed of a gold germanium nickel layer (AuGeNi) and a first gold layer, and the selection of these materials and the structural design play a crucial role in electronic devices.
[0049] Specifically: Composition of the AuGeNi layer: AuGeNi is an alloy, usually composed of gold (Au), germanium (Ge), and nickel (Ni). This alloy is used as an electrode material in semiconductor devices and is particularly suitable for connection with silicon-based materials (such as substrate layer 2). The AuGeNi alloy has excellent contact performance at relatively low temperatures and can form low-resistance contacts between metals and semiconductors.
[0050] Thickness requirement of the AuGeNi layer: The thickness range of the AuGeNi layer is 40 - 60 nanometers. This thickness range can ensure good contact performance between the AuGeNi layer and the substrate, ensuring that current can be effectively conducted to substrate layer 2, while avoiding excessive thickness between layers that may lead to too large contact resistance and thus affecting device performance.
[0051] Connected to substrate layer 2: The AuGeNi layer is directly connected to substrate layer 2. This design ensures that the lower electrode layer 1 can form a stable electrical contact on the substrate surface. Substrate layer 2 is usually silicon, germanium, or other semiconductor materials, and the choice of AuGeNi can ensure good interfacial connection between the substrate and the electrode and achieve low-resistance, high-stability contact.
[0052] Composition of the first gold layer (Au): The first gold layer is a pure gold (Au) layer and is part of the electrode. Gold has excellent electrical conductivity, corrosion resistance, and good welding performance and is widely used in electrode layers in electronic devices, especially in cases where high stability and low contact resistance are required.
[0053] Thickness requirement of the first gold layer: The thickness of the first gold layer is at least 2000 nanometers. This thickness can ensure the conductive function of the gold layer in the electrode and at the same time provide sufficient mechanical strength to support subsequent connection and welding processes. A thicker gold layer can effectively reduce contact resistance and improve the durability of the electrode, especially in high-temperature or long-term use cases.
[0054] In addition, the AuGeNi layer and the first gold layer are formed into the lower electrode layer 1 through the magnetron sputtering process. Magnetron sputtering is a physical vapor deposition (PVD) technology commonly used for depositing thin film materials on substrates. This process bombards the target material with high-energy ions, causing target atoms or molecules to sputter onto the substrate to form a thin film.
[0055] By depositing the AuGeNi layer and the gold layer through the magnetron sputtering process, the thickness and composition of the thin film can be precisely controlled. This process can provide a uniform and dense film layer, ensuring high quality, good adhesion, and appropriate electrical performance of the electrode layer. In addition, the magnetron sputtering process can also be carried out at relatively low temperatures, which is crucial for avoiding damage to the substrate or other device layers.
[0056] It should be noted that the main function of the electrode layer is to provide a low-resistance contact path for the current in the electronic device to flow through the electrode, while ensuring stable contact between the electrode and the substrate during long-term operation. The AuGeNi layer provides good contact with the substrate, while the thick Au layer provides sufficient current conduction ability and ensures the mechanical stability of the electrode.
[0057] Through the reasonable combination of the AuGeNi layer and the first Au layer, the lower electrode layer 1 fabricated by the magnetron sputtering process can provide excellent electrical performance, good mechanical strength and stability. The appropriate thickness of the AuGeNi layer and its good contact with the substrate effectively reduce the contact resistance, while the thick Au layer ensures conductivity and durability, meeting the requirements of various electronic devices for the electrode layer.
[0058] In a possible implementation, the material of the substrate layer 2 is N-type doped gallium arsenide (GaAs). N-type doping means that pentavalent elements (such as phosphorus, arsenic, etc.) are doped into the gallium arsenide material to make it an N-type semiconductor. This doping increases the number of free electrons, improves the conductivity of the material, enables it to provide free electrons, and thus endows the material with certain conductivity. The choice of GaAs as the substrate material is because it has excellent electronic and optical properties, such as high carrier mobility, low optical absorption loss, etc., which are crucial for the performance of the laser.
[0059] In terms of thickness, the thickness of the substrate layer 2 is 90 - 100 microns. This thickness range ensures that the substrate layer 2 has sufficient mechanical strength to support other layer materials and helps to ensure the stability and reliability of the laser. In addition, the appropriate thickness can effectively match with other material layers (such as the lower DBR layer 3, the lower waveguide layer 5, etc.), ensuring good bonding of each layer and optimization of the overall performance.
[0060] In a possible implementation, the lower DBR layer 3 includes 30 to 40 pairs of aluminum gallium arsenide alloy reflector layers. These reflector layers are arranged alternately to form the Bragg reflection effect through different material structures for efficiently reflecting light of the laser wavelength. The relatively large number of these reflector layers is to enhance the reflection effect and make the performance of the laser more excellent.
[0061] The material of the aluminum gallium arsenide alloy reflector layer is mainly composed of aluminum gallium arsenide alloy. There are two choices for the composition ratio of this alloy:
[0062] (1) Aluminum gallium arsenide alloy (Al 0.1 GaAs) with 10% aluminum: This alloy reflector layer has a lower refractive index and is used to form reflections of longer wavelengths.
[0063] (2) Aluminum gallium arsenide alloy (Al 0.9(GaAs): This alloy reflector has a relatively high refractive index, enabling a stronger reflection effect.
[0064] The refractive index differences of each alloy material help achieve the desired reflection wavelength in the laser, thereby enhancing the reflection efficiency.
[0065] Optical thickness of the reflector: The optical thickness of each aluminum gallium arsenide alloy reflector layer is equal to one - quarter of the lasing wavelength of the laser. This design is crucial for the Bragg reflector. The one - quarter - wavelength thickness allows each pair of reflector layers to achieve maximum reflection at that specific wavelength. By precisely controlling the thickness of each layer, the wavelength output of the laser can be effectively adjusted.
[0066] Gradual change characteristics of the reflector: The two sub - layers of each pair of aluminum gallium arsenide alloy reflector layers have a compositional gradual change characteristic, that is, the material composition in each pair of reflector layers changes gradually with depth. The gradual change characteristic helps reduce the reflection loss of light and improve the reflection efficiency. Through the gradual change of material composition, the laser can reduce the reduction of reflection efficiency caused by the refractive index mismatch of materials.
[0067] N - type doping concentration: In the lower DBR layer 3, the N - type doping concentration of the two pairs of aluminum gallium arsenide alloy reflector layers adjacent to the quantum well layer 6 is less than or equal to 4×10 17 per cubic centimeter. The control of doping concentration is crucial for the performance of the laser. The reason for the lower N - type doping concentration is to reduce the carrier aggregation caused by doping, thus avoiding affecting the laser emission performance of the quantum well.
[0068] For the other aluminum gallium arsenide alloy reflector layers in the lower DBR layer 3, the N - type doping concentration is 4×10 17 to 2×10 18 per cubic centimeter. The higher N - type doping concentration of these reflector layers helps improve the conductivity of the reflector layer, ensuring uniform current distribution in the laser. The reasonable doping concentration enables the current to flow more smoothly in the laser, while avoiding thermal effects or optical losses caused by too high doping concentration.
[0069] The design of the lower DBR layer 3 effectively optimizes the optical and electrical properties of the laser by reasonably controlling the ratio of aluminum gallium arsenide alloy, optical thickness, the gradual change characteristics of the material, and the N - type doping concentration. Precise material selection and structural design ensure the high efficiency, stability, and long service life of the laser.
[0070] In a possible implementation, the material of the lower spacer layer 4 is indium gallium arsenide phosphide alloy (InGaAsP) or aluminum gallium indium arsenide alloy (AlGaInAs) with an unintentional doping concentration less than 1×10 18 per cubic centimeter.
[0071] Specifically, the chemical composition of InGaAsP: InGaAsP is a compound composed of indium (In), gallium (Ga), arsenic (As), and phosphorus (P). Its composition ratio can be adjusted to achieve different bandgap widths and properties. This material is widely used in optoelectronics, especially in the manufacture of lasers, photodetectors, and optical modulators, because it can adjust the bandgap to adapt to different wavelengths.
[0072] The chemical composition of AlGaInAs: AlGaInAs is an alloy composed of aluminum (Al), gallium (Ga), indium (In), and arsenic (As), with adjustable bandgap characteristics. It is widely used in high-efficiency optoelectronic devices and integrated optoelectronic circuits.
[0073] Doping concentration requirement: The doping concentration of the material should be less than 1×10 18 per cubic centimeter. This is to ensure that the material is not over-doped, thereby maintaining a low carrier concentration and low conductivity. A lower doping concentration can avoid non-radiative recombination caused by excessive carriers, which in turn affects the performance of the device. Especially in lasers or optical modulators, too high a doping concentration may lead to reduced efficiency.
[0074] The thickness of the lower spacer layer 4: The thickness of the lower spacer layer 4 ranges from 200 to 400 nanometers. The thickness range of 200 - 400 nanometers is very important for the design of the lower spacer layer 4. This thickness range can generally effectively achieve the following functions:
[0075] (1) Optical isolation: The lower spacer layer 4 is commonly used as an optical isolation layer in optoelectronic devices to help reduce mutual interference between different layers inside the device. An appropriate thickness can ensure the optical isolation performance of the optical waveguide or optical fiber.
[0076] (2) Current control: For lasers or photodiodes, the thickness of the lower spacer layer 4 can help control the current flow direction, ensure uniform current distribution in the structure, and prevent carrier aggregation or unnecessary recombination effects.
[0077] (3) Bandgap adjustment: The thickness of the lower spacer layer 4 is also closely related to bandgap adjustment. The thickness can be combined with the bandgap width of the material to control the operating wavelength or performance of the device.
[0078] The refractive index of the lower spacer layer 4: The refractive index is an important parameter describing the propagation speed of light in a material. In semiconductor materials, the refractive index not only affects the propagation speed of light but also affects the mode structure of the optical waveguide. The refractive index of the lower spacer layer 4 is 3.3. The relatively high refractive index indicates that this material can effectively confine light waves within a specific wavelength range, ensuring that light waves can propagate in the waveguide or other optical structures.
[0079] In optoelectronic devices, refractive index matching is crucial for constructing efficient optical waveguides and ensuring light propagation. Materials with a refractive index of 3.3 are suitable for use in high-speed and high-efficiency optical communication systems, especially in devices that require strong beam confinement.
[0080] High refractive index materials generally can provide stronger beam confinement force, which is beneficial to reducing light loss in the device and improving the overall optoelectronic conversion efficiency. In optoelectronic devices with a multi-layer structure, appropriate refractive index differences can effectively control the propagation of light and avoid light leakage or unnecessary scattering.
[0081] The material, thickness, and refractive index selection of the lower spacer layer 4 are the keys to designing high-performance optoelectronic devices. Using InGaAsP or AlGaInAs as the material and controlling its doping concentration, thickness (200 - 400 nanometers), and refractive index (3.3) contribute to optimizing the optoelectronic performance, current control, and optical isolation performance of the device. Precise control of these parameters is the basis for ensuring the stable and efficient performance of optoelectronic devices during operation.
[0082] The role of the lower waveguide layer 5 in a laser is to guide light and ensure that the laser can effectively propagate from the quantum well of the laser. The material selection of the lower waveguide layer 5 is crucial for the performance of the laser. The refractive index, bandgap structure, and conductivity of the material will all affect the output efficiency and stability of the laser.
[0083] In a possible implementation, the material of the lower waveguide layer 5 is InGaAsP or AlGaInAs, the thickness is 200 - 300 nanometers, and the unintentional doping concentration is less than 2×10 17 per cubic centimeter.
[0084] Specifically, InGaAsP: InGaAsP is an alloy material with good optical and electrical properties, especially having advantages in wavelength tuning. By adjusting the ratios of In, Ga, As, and P, the bandgap of this material can be adjusted to enable the laser to operate in different wavelength ranges. InGaAsP materials are commonly used in lasers with longer wavelengths (such as lasers in the 1.3μm and 1.5μm wavelength ranges).
[0085] AlGaInAs: The AlGaInAs alloy is widely used in semiconductor lasers, especially in lasers in the wavelength range of 1.3μm to 1.55μm, with good temperature stability and low threshold current characteristics. Its bandgap and refractive index can be precisely controlled by adjusting the ratios of Al, Ga, In, and As. Therefore, it is often used as the material for the waveguide layer in the design of high-efficiency lasers.
[0086] Thickness of the lower waveguide layer 5: The thickness of the lower waveguide layer 5 is 200 - 300 nanometers. This thickness range is designed based on the light propagation characteristics of the waveguide. In a laser, the thickness of the waveguide layer needs to be thick enough to ensure effective light propagation therein and avoid light leakage or mode instability caused by an overly thin waveguide layer. The thickness range of 200 - 300 nanometers can ensure good light guiding and avoid light loss caused by an overly large thickness. This thickness range is generally applicable to vertical cavity surface emitting lasers (VCSELs) or edge-emitting lasers, especially those lasers that require a precise waveguide structure to ensure effective enhancement and excitation of light in the quantum well.
[0087] Unintentional doping concentration of the lower waveguide layer 5: The unintentional doping concentration of the lower waveguide layer 5 is less than 2×10 17 per cubic centimeter. Unintentional doping refers to the impurity concentration in the material that has not undergone an intentional doping process, usually caused by impurities in the manufacturing process or impure substances in the raw materials. This concentration range indicates that although the lower waveguide layer 5 may contain a certain amount of impurities or dopants, its doping concentration remains at a relatively low level. This is very important for a laser because too high an impurity concentration will cause carrier recombination, light loss, or current leakage, thereby affecting the efficiency and stability of the laser.
[0088] The requirement that the unintentional doping concentration is less than 2×10 17 per cubic centimeter generally means that this waveguide layer has a relatively low carrier concentration, thus reducing the thermal loss and current leakage caused by carrier recombination. In addition, the lower doping concentration helps maintain a lower electric field near the quantum well layer 6, thereby avoiding disrupting the laser emission process of the quantum well.
[0089] It should be noted that the main function of the lower waveguide layer 5 is to guide light and ensure that the light propagation path does not scatter. The lower waveguide layer 5 forms a light propagation channel by working together with the upper waveguide layer. Its material and structural characteristics have important effects on aspects such as mode control, laser output efficiency, thermal management, and current distribution of the laser.
[0090] Due to the positional relationship between the waveguide layer and the quantum well layer 6, the lower waveguide layer 5 also needs to play a role in controlling the light beam under a specific current. By reasonably designing the material and thickness of the waveguide layer, the current-light output characteristics of the laser can be optimized to achieve a lower threshold current and a higher laser efficiency.
[0091] The lower quantum well layer 6 is an important structural layer in a semiconductor laser, which directly affects the generation and performance of the laser. In a possible implementation, the material of the lower quantum well layer 6 has an unintentional doping concentration less than 1×10 17InGaAs or AlGaAs per cubic centimeter.
[0092] Specifically, material selection for the lower quantum well layer 6: The material of the lower quantum well layer 6 can be InGaAs or AlGaAs. These materials have extensive applications in semiconductor lasers, especially when used in combination with quantum well structures.
[0093] InGaAs: InGaAs is a material with a relatively small bandgap, suitable for long-wavelength lasers, especially those operating in communication wavelength ranges such as 1.3 μm and 1.55 μm. The bandgap of InGaAs material can be adjusted according to the indium content, and it has excellent optical properties, especially outstanding performance in the photoelectric effect.
[0094] AlGaAs: AlGaAs is commonly used in lasers in the infrared wavelength range. By adjusting the ratio of aluminum and gallium, the bandgap of the material can be adjusted to meet the requirements of different wavelengths. The high bandgap characteristic of AlGaAs material can provide excellent electronic, optical, and thermal properties, suitable for efficient laser emission.
[0095] Unintentional doping concentration: The unintentional doping concentration of the lower quantum well layer 6 is less than 1×10 17 per cubic centimeter. This indicates that the doping concentration of this layer is relatively low, avoiding excessive impurities causing carrier recombination or affecting optical properties. The low doping concentration helps to improve the carrier mobility of the material, reduce current leakage, and improve the efficiency of the laser.
[0096] Thickness range of the lower quantum well layer 6: The thickness of the lower quantum well layer 6 is 20 - 100 nanometers. The selection of this thickness range is mainly closely related to the optical and electronic properties of the quantum well. An appropriate thickness helps to form a stable energy level structure within the quantum well, thus effectively carrying out optical excitation and radiative recombination.
[0097] In a quantum well, electrons and holes will combine within the well layer to form an excited state, and finally emit light through radiative recombination. If the quantum well layer 6 is too thin, it may not be able to accommodate enough electrons and holes, resulting in low laser efficiency; while if the quantum well layer 6 is too thick, it may lead to too fast carrier diffusion and a decrease in the light recombination efficiency. Therefore, the thickness range of 20 - 100 nanometers provides a good balance, ensuring sufficient carrier accumulation and effective optical behavior.
[0098] Sub - quantum well structure of the lower quantum well layer 6: The lower quantum well layer 6 is composed of multiple sub - quantum wells, including 1 to 5 sub - quantum wells. These sub - quantum wells include well layers and barrier layers. Each sub - quantum well is usually composed of two materials with different band structures. Additionally, the number of sub - quantum wells is an important factor affecting the light - emitting efficiency and gain characteristics of the quantum well layer 6. Increasing the number of sub - quantum wells helps improve the light gain, but too many sub - quantum wells may cause carrier saturation or thermal effects.
[0099] Well layer and barrier layer: Each sub - quantum well includes a well layer and a barrier layer. The well layer is the part of the quantum well with a smaller bandgap, usually composed of InGaAs or other similar materials. Electrons and holes combine in the well layer to form an excited state and emit light through radiative recombination. The thickness of the well layer is usually 4 - 8 nanometers. This thickness range can ensure the effective combination of electrons and holes in this region, while avoiding the too - fast diffusion of electrons and holes due to excessive thickness, which reduces the recombination efficiency. The barrier layer is the part of the quantum well with a larger bandgap, usually composed of materials such as AlGaAs. The role of the barrier layer is to confine electrons and holes within the well layer, preventing them from escaping outward, thereby improving the light - emitting efficiency of the laser. The thickness of the barrier layer is usually 6 - 10 nanometers. This thickness can ensure a good confinement effect while avoiding the change of the band structure due to excessive thickness, which affects the optical and electrical properties of the quantum well.
[0100] It should be noted that the main role of the lower quantum well layer 6 in the semiconductor laser is to enhance the light emission through the quantum confinement effect. When electrons and holes recombine within the well layer, they release energy to generate light. By precisely designing the structure and materials of the lower quantum well layer 6, the output power, wavelength, efficiency, and stability of the laser can be optimized.
[0101] In the design of semiconductor lasers, the design of the upper spacer layer 8 (usually located between the quantum well layer 6 and other layers) is a key part, which has an important impact on the performance, efficiency, and stability of the laser.
[0102] In a possible implementation, the material of the upper spacer layer 8 has a doping concentration less than 1×10 18 per cubic centimeter of AlGaAs. The thickness of the upper spacer layer 8 is 200 - 400 nanometers, and the refractive index of the upper spacer layer 8 is 2.9.
[0103] Specifically, the material and doping concentration of the upper spacer layer 8: The upper spacer layer 8 uses AlGaAs (aluminum gallium arsenide alloy). The AlGaAs material has an adjustable bandgap. By adjusting the ratio of aluminum (Al) and gallium (Ga), the optical and electronic properties of the material can be controlled. AlGaAs has a relatively high bandgap, so it can be used as an isolation layer in the laser to prevent carrier leakage to other regions and ensure the generation and transmission of laser light.
[0104] Doping concentration of the upper spacer layer 8: The doping concentration of the upper spacer layer 8 is less than 1×10 18 per cubic centimeter. This doping concentration typically represents the n-type or p-type doping of the upper spacer layer 8, whose function is to adjust the carrier concentration, control the conductivity and carrier distribution of the material. The upper spacer layer 8 is usually lightly doped because its main function is to provide electrical field isolation rather than directly participate in current transmission. A lower doping concentration helps reduce carrier recombination and scattering, optimizing the operating efficiency of the laser.
[0105] Thickness of the upper spacer layer 8: The thickness of the upper spacer layer 8 ranges from 200 to 400 nanometers. The thickness selection has an important impact on the performance of the semiconductor laser: The thickness of the upper spacer layer 8 not only affects the isolation effect but also affects the optical performance, waveguide characteristics and carrier distribution of the laser. A thickness range of 200 - 400 nanometers can provide an effective current isolation function while ensuring good optical waveguide effects. If the upper spacer layer 8 is too thin, it may not effectively isolate the current, resulting in carrier leakage into the quantum well layer 6 or other regions, thereby reducing the efficiency and stability of the laser. If the upper spacer layer 8 is too thick, it may increase the pumping current and operating voltage of the laser, causing energy loss. Therefore, a thickness of 200 - 400 nanometers can balance current isolation and optical effects.
[0106] Refractive index of the upper spacer layer 8: The refractive index of the upper spacer layer 8 is 2.9, which is one of the optical properties of the material. The refractive index determines the propagation speed of light waves in the material, thereby affecting the beam propagation and optical mode distribution in the waveguide layer. A high refractive index helps effectively confine the light beam within the waveguide layer, thereby improving the output efficiency of the laser. A material with a refractive index of 2.9 has a relatively high optical density, ensuring the propagation effect of light within the laser. The refractive index difference causes light to be reflected in the waveguide structure and propagate along a predetermined path. Therefore, the upper spacer layer 8 with a refractive index of 2.9 plays an important role in the design of the waveguide layer, ensuring effective light propagation and good optical mode control.
[0107] Growth rate of the upper spacer layer 8 is related to the upper waveguide layer 7: The upper spacer layer 8 is located above the upper waveguide layer 7, and the strip waveguides in the upper waveguide layer 7 gradually change according to a periodic arithmetic progression. The structure and width differences of these strip waveguides directly affect the growth process of the waveguide layer. The width of each strip waveguide in the upper waveguide layer 7 is different, resulting in different surface structures and surface energies in the underlying regions. Strip waveguides with different widths will have different effects on the diffusion rate and adsorption behavior of gas molecules or atoms during deposition, which will lead to spatial variations in the growth rate.
[0108] Growth rate of the wide-strip region: In the wider strip waveguide region, the deposited gas molecules or atoms can be deposited more evenly on the surface of this region because the wider region has more surface for gas molecules to deposit. Due to the larger surface area, the deposition rate is relatively fast.
[0109] Growth rate of the narrow-strip region: In the narrower strip waveguide region, due to the smaller surface area, the chance of gas molecules or atoms to deposit decreases, resulting in a slower deposition rate in these regions. In addition, the narrow region may cause more intensive collisions and diffusion of gas molecules or atoms, thereby affecting the deposition manner and rate.
[0110] Relationship between the arithmetic progression of width change and the growth rate: Since the width of the strip waveguide changes in an arithmetic progression and the width of each region is different, this periodic change will also affect the gas distribution during deposition. In some regions, due to the width change, the concentration and distribution of the deposited material may be different, resulting in differences in the local growth rate. Specifically: as the width of the strip waveguide gradually increases or decreases, the deposition rate will change accordingly, resulting in different waveguide layer thicknesses on different regions, further affecting the optical properties of the waveguide layer.
[0111] The upper waveguide layer 7 not only affects the deposition rate but also the diffusion behavior of the material on the surface. In regions with different strip waveguide widths, both the diffusion rate and the deposition rate will be different, resulting in different growth rates in different regions. This structured growth environment causes changes in the optical and electrical properties of each region. The patterned periodic distribution, that is, the characteristic that the width of the filling material changes in an arithmetic progression, will affect optical parameters such as the thickness distribution and refractive index distribution of the entire upper waveguide layer, thereby affecting the performance of the laser. The periodic change in the growth rate will directly affect the optical mode, beam propagation, reflection and other performances of the waveguide layer.
[0112] The upper DBR layer 9 is an important structural part in the semiconductor laser. Its main function is to provide strong reflection to ensure the effective reflection and enhancement of the optical mode of the laser in the laser cavity. The design of the upper DBR layer 9 directly affects the efficiency, output power and optical stability of the laser.
[0113] In a possible implementation, the upper DBR layer 9 includes multiple alloy reflection layers, and each alloy reflection layer includes 18 to 24 pairs of aluminum gallium arsenide alloy reflection layers. The design of the alloy reflection layer adopts multiple columnar structures arranged parallel to the arrangement direction of the strip waveguide. This design presents an ellipse with a major axis parallel to the strip waveguide in the cross-section parallel to the extension direction of the upper spacer layer. Such a design can effectively control the propagation path of light and play a good reflection role. And between the multiple columns, silicon dioxide (SiO2) and / or silicon nitride (Si3N4) are filled.
[0114] Specifically, the composition of the upper DBR layer 9: The upper DBR layer 9 is composed of multiple alloy reflection layers ( Figure 1 wherein, a black shadow in the upper DBR layer 9 represents an alloy reflection layer), and each reflection layer includes 18 to 24 pairs of aluminum gallium arsenide alloy reflection layers. These reflection layers enhance the reflectivity through a multi-layer structure, increase the reflection of specific wavelengths, and thereby improve the optical quality of the laser.
[0115] AlGaAs reflection layer: These reflection layers are made of aluminum gallium arsenide alloy materials, with different ratios of aluminum and gallium, resulting in different bandgaps and adjusting the reflection characteristics. The change in aluminum content controls the refractive index difference of the material, thereby affecting the reflection intensity.
[0116] Material characteristics of the AlGaAs reflection layer: In the aluminum gallium arsenide alloy of the reflection layer material, the proportion of aluminum is 10% or 90%. Different aluminum ratios will affect the refractive index and bandgap of the reflection layer. Therefore, the ratio of aluminum gallium arsenide alloy is selected during design to achieve the desired reflection characteristics and the operating wavelength of the laser.
[0117] Aluminum gallium arsenide alloy with 10% aluminum (Al 0.1 GaAs): It has a lower bandgap and refractive index.
[0118] Aluminum gallium arsenide alloy with 90% aluminum (Al 0.9 GaAs): It has a higher bandgap and refractive index.
[0119] Optical thickness of the reflection layer: The optical thickness of each aluminum gallium arsenide alloy reflection layer in the upper DBR layer 9 is one-fourth of the lasing wavelength of the laser. The optical thickness refers to the thickness of the material relative to the wavelength in the direction of light wave propagation. The design of one-fourth wavelength can ensure that the reflected wavefront phases of each pair of reflection layers are completely coherent, thereby forming a strong reflection. In optical design, by adjusting the optical thickness of each reflection layer to one-fourth of the wavelength, the reflection efficiency can be effectively enhanced. This design can enhance the reflection of light, thereby improving the gain and efficiency of the laser.
[0120] Composition gradient characteristics of the reflection layer: The two sub-layers of each pair of aluminum gallium arsenide alloy reflection layers have composition gradient characteristics. That is, the aluminum gallium ratio of these reflection layers is not fixed but gradually changes, which helps to reduce the interfacial stress between layers, improve the contact quality between layers, reduce material inhomogeneity, and improve the stability of the laser. The gradually changing composition helps to reduce the optical loss and stress at the interface of the reflection layer caused by the abrupt change in the refractive index of the material, thereby improving the reflection efficiency and structural stability.
[0121] P doping concentration distribution: In the upper DBR layer 9, the P doping concentration of the two pairs of aluminum gallium arsenide alloy reflection layers adjacent to the active region should be lower than 4×10 17per cubic centimeter, while the P doping concentration of the remaining reflective layers ranges from 4×10 17 to 2×10 18 per cubic centimeter. The P doping concentration determines the conductivity of the material. A lower doping concentration can reduce carrier recombination and losses. For the upper DBR layer 9, especially in the region close to the active region, a lower P doping concentration helps reduce current leakage in the laser and improve the optical reflection effect.
[0122] High aluminum layer and alumina: In the upper DBR layer 9, a high aluminum layer is provided on the side close to the upper spacer layer 8, and this high aluminum layer has been oxidized to alumina (Al 2 O 3 ). The role of the high aluminum layer is to enhance electrical and optical isolation and improve the stability of the material. Alumina has a high dielectric constant and can effectively isolate current leakage and heat loss between different layers. The presence of alumina makes the structure of the upper DBR layer 9 more stable and reliable.
[0123] Highly doped contact layer: A highly doped contact layer is provided at the top of the upper DBR layer 9, and its thickness is 20 nanometers. The role of the highly doped contact layer is to provide good current conductivity to ensure that current can be effectively transmitted to the active region of the laser. Through highly doped materials, low-resistance contact can be achieved, reducing losses and thermal effects during current flow and improving the operating efficiency of the laser.
[0124] Silicon oxide and silicon nitride isolation: Starting from the upper DBR layer 9, the laser array has been formed, and the alloy reflective layers are isolated by silicon oxide (SiO 2 ) and silicon nitride (Si 3 N 4 ) materials ( Figure 1 in, the white shaded part in the upper DBR layer 9 is the filling material). Silicon oxide and silicon nitride materials have good electrical and optical isolation properties and can effectively isolate different laser units to prevent mutual interference. These materials not only play an optical isolation role but also prevent electrical short circuits and interference between different lasers, ensuring that each laser unit operates independently and improving the stability and performance of the overall laser array.
[0125] The design of the upper DBR layer 9, especially the multi-layer structure, gradient characteristics, doping concentration distribution of the aluminum gallium arsenide alloy reflective layer, the setting of the alumina layer, the thickness of the highly doped contact layer, and the isolation measures of silicon oxide and silicon nitride, are all to ensure that the semiconductor laser operates at high efficiency, low loss, and high stability. Each design parameter has been precisely adjusted to improve the output power, efficiency, and long-term reliability of the laser.
[0126] The upper DBR layer 9 is an important part of the laser structure and is responsible for reflecting a specific wavelength of laser light. Starting from the upper DBR layer 9, the laser array is formed. That is to say, starting from this layer of the upper DBR layer 9, the entire array structure of the laser gradually takes shape, and each laser unit already begins to have the ability to emit laser light.
[0127] It should be noted that a "laser unit" refers to each independent laser-emitting unit in the VCSEL array. In a multi-wavelength high-polarization VCSEL array, each laser unit is a separate unit capable of independently emitting laser light. They are usually oval-shaped (see Figure 2 ), with dimensions between 20 - 40 microns, and the long side direction of them is arranged along the vertical bars on the upper waveguide layer 7.
[0128] Due to the design of the patterned structure, the emission wavelengths of these laser units will be different. The optical properties of each unit, such as the emission wavelength or polarization, are affected by its patterned structure, waveguide design, and other material properties. In short, the laser units are the independent laser sources in the VCSEL array, and their shapes, sizes, and emission wavelengths may all vary due to the design.
[0129] It also needs to be noted that the laser unit is a key component when describing the overall structure of the VCSEL array, but it is not a separate layer or component in 1 - 10. The laser unit is a light-emitting structure formed by multiple layers. Specifically, through the combined action of layers such as the "upper waveguide layer 7" and the "upper DBR layer 9", individual laser-emitting regions are formed in the array. Among them, the distribution design of the strip waveguides in the "upper waveguide layer 7" is the key to forming laser units with different wavelengths, and the "upper DBR layer 9" acts together with the upper waveguide layer 7 and the upper spacer layer 8 to endow each laser unit with specific optical properties.
[0130] The specific manifestation form and characteristics of the laser unit are jointly determined by the structure of the upper waveguide layer 7 and the setting of the upper DBR layer 9. Each oval laser unit is actually constructed by a specific pattern on the upper waveguide layer and the upper DBR layer 9. Each unit realizes different wavelength emissions through its unique geometric dimensions and has specific polarization characteristics.
[0131] In a possible implementation, the upper electrode layer 10 is composed of a titanium layer and a second gold layer. The thickness of the titanium layer is 50 - 100 nanometers, and the thickness of the second gold layer is at least 300 nanometers. This structure is commonly used in microelectronic devices and optoelectronic devices as electrode materials, with good electrical conductivity and reliable contact performance. Now let's analyze the purpose of this design and its possible impacts:
[0132] Function of the titanium layer: Conductivity and adhesiveness of the titanium layer: The titanium layer is usually used as a transition layer between a metal electrode and other materials. Titanium has good adhesiveness, which can improve the adhesion of the second gold layer and ensure the stability of the electrode during long-term use. Titanium can also provide a good conduction path between the electrode and the substrate.
[0133] Thickness of titanium: The thickness of the titanium layer is set to be 50 - 100 nanometers, which is usually sufficient to ensure that titanium can effectively adhere to the underlying material, while avoiding the influence of an overly thick titanium layer on the electrical properties of other layers. This thickness range can balance the adhesion performance and conductivity of titanium.
[0134] Function of the second gold layer: Gold (Au) has extremely high conductivity and chemical stability, and is a commonly used choice for electrode materials. The thickness of the gold layer is relatively thick, usually greater than 300 nanometers, aiming to provide sufficient conduction paths to ensure the smooth flow of current.
[0135] Thickness of the second gold layer: The thickness of the second gold layer is at least 300 nanometers. Such a design can ensure that the gold layer will not lose its good conductivity and stability due to oxidation or wear during long-term use. The relatively thick thickness of the gold layer can reduce the contact resistance and improve the current-carrying capacity and reliability of the device.
[0136] In the embodiments of the present application, by adopting a special material patterning design in the upper waveguide layer structure, the difference in growth rate is successfully achieved, thereby precisely controlling the thickness difference of the spacer layer, and further adjusting the lasing wavelength of the laser. This innovative design makes the production of multi-wavelength, high-polarization array surface-emitting lasers more efficient and economical, while improving the flexibility and controllability during the production process. Compared with the high cost and technical difficulties of using sub-wavelength gratings in traditional methods, the present application effectively reduces the cost and provides new opportunities and development space for the production of multi-wavelength lasers.
[0137] It should be noted that the various embodiments in this specification are described in a progressive manner. The same or similar parts among the various embodiments can be referred to each other. Each embodiment focuses on the differences from other embodiments. For the relevant parts, refer to the partial description of the method embodiments. The laser structure and method embodiments described above are only illustrative, and some or all of the modules can be selected according to actual needs to achieve the purpose of the solution of this embodiment. Those of ordinary skill in the art can understand and implement it without creative work.
[0138] As described above, it is only a specific implementation manner of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed in the present application should be covered within the protection scope of the present application. Therefore, the protection scope of the present application should be subject to the protection scope of the claims.
Claims
1. A multi-wavelength high-polarization straight-cavity surface-emitting laser, characterized in that: The laser comprises a lower electrode layer, a substrate layer, a lower distributed Bragg reflector DBR layer, a lower spacer layer, a lower waveguide layer, a quantum well layer, an upper waveguide layer, an upper spacer layer, an upper DBR layer and an upper electrode layer stacked in sequence; The upper waveguide layer includes a plurality of strip waveguides with different widths arranged in parallel in the same plane, and a filling material filled between the plurality of strip waveguides; the widths of the plurality of strip waveguides vary in a periodic arithmetic progression.
2. The laser according to claim 1, characterized in that The material of the upper waveguide layer is indium gallium arsenic phosphide InGaAsP or aluminum gallium indium arsenide AlGaInAs with an unintentional doping concentration of less than 2×1017 per cubic centimeter; the thickness of the upper waveguide layer is 200-400 nanometers; the width of each strip waveguide in the upper waveguide layer is different, the width of each strip waveguide is 2-10 microns, and the strip waveguides in the upper waveguide layer form a periodic distribution according to the width change of an arithmetic progression; the filling material is aluminum gallium arsenide AlGaAs with a refractive index equal to 2.
9.
3. The laser according to claim 1, characterized in that The lower electrode layer comprises a stacked gold-germanium-nickel layer and a first gold layer; the gold-germanium-nickel layer is located on a side of the lower electrode layer in contact with the substrate layer; Wherein, the thickness of the gold-germanium-nickel layer is 40-60 nanometers; the thickness of the first gold layer is at least 2000 nanometers; the gold-germanium-nickel layer and the first gold layer are formed by a magnetron sputtering process.
4. The laser according to claim 1, characterized in that The lower DBR layer comprises 30 to 40 pairs of aluminum gallium arsenic alloy reflective layers; Among them, the material of the aluminum-gallium-arsenic alloy reflective layer includes an aluminum-gallium-arsenic alloy with an aluminum ratio of 10%, or an aluminum-gallium-arsenic alloy with an aluminum ratio of 90%; the optical thickness of each layer of the aluminum-gallium-arsenic alloy reflective layer is equal to one quarter of the lasing wavelength of the laser; the two sublayers in each pair of the aluminum-gallium-arsenic alloy reflective layers have a component gradient characteristic; in the lower DBR layer, the materials of the two aluminum-gallium-arsenic alloy reflective layers close to the quantum well layer have an N-type doping concentration less than or equal to 4X1017 per cubic centimeter, and the N-type doping concentration of other aluminum-gallium-arsenic alloy reflective layer materials in the lower DBR layer is 4X1017-2X1018 per cubic centimeter.
5. The laser according to claim 1, characterized in that The material of the lower spacer layer is InGaAsP or AlGaInAs with an unintentional doping concentration of less than 1×1018 per cubic centimeter; Wherein, the thickness of the lower spacer layer is 200-400 nanometers; and the refractive index of the lower spacer layer is 3.
3.
6. The laser according to claim 1, characterized in that The material of the lower waveguide layer is InGaAsP or AlGaInAs, with a thickness of 200-300 nanometers and an unintentional doping concentration of less than 2×10 17 per cubic centimeter.
7. The laser according to claim 1, characterized in that The material of the lower quantum well layer is InGaAs or AlGaAs with an unintentional doping concentration of less than 1×1017 per cubic centimeter; Among them, the thickness of the lower quantum well layer is 20-100 nanometers; the lower quantum well layer contains 1-5 sub-quantum wells, and the sub-quantum wells include a well layer and a barrier layer; the thickness of the well layer is 4-8 nanometers; the thickness of the barrier layer is 6-10 nanometers.
8. The laser according to claim 1, characterized in that The material of the upper spacer layer is AlGaAs with a doping concentration less than 1×1018 per cubic centimeter; the thickness of the upper spacer layer is 200-400 nanometers; and the refractive index of the upper spacer layer is 2.
9.
9. The laser according to claim 1, characterized in that The upper DBR layer comprises a plurality of alloy reflective layers; each of the alloy reflective layers comprises 18 to 24 pairs of aluminum-gallium-arsenic alloy reflective layers; The material of the aluminum-gallium-arsenic alloy reflective layer includes an aluminum-gallium-arsenic alloy with an aluminum ratio of 10%, or an aluminum-gallium-arsenic alloy with an aluminum ratio of 90%; the optical thickness of each layer of the aluminum-gallium-arsenic alloy reflective layer is equal to one-fourth of the lasing wavelength of the laser; the two sublayers of each pair of the aluminum-gallium-arsenic alloy reflective layer have a component gradient feature; the P doping concentration of the two pairs of the aluminum-gallium-arsenic alloy reflective layer materials adjacent to the active area in the upper DBR layer is not greater than 4X1017 per cubic centimeter, and the P doping concentration of the other pairs of the aluminum-gallium-arsenic alloy reflective layer materials in the upper DBR layer is 4X1017-2X1018 per cubic centimeter; The upper DBR layer also includes a high aluminum layer, which is located on the side of the upper DBR layer in contact with the upper spacer layer; a highly doped contact layer is provided on the top of the upper DBR layer, and the thickness of the highly doped contact layer is 20 nanometers; the alloy reflective layer is a plurality of columns arranged in parallel along the arrangement direction of the strip waveguide, and the cross section parallel to the extension direction of the upper spacer layer is an ellipse with a long diameter parallel to the strip waveguide; silicon oxide and / or silicon nitride are filled between the plurality of columns.
10. The laser according to claim 1, characterized in that The upper electrode layer includes a titanium layer and a second gold layer; Wherein, the thickness of the titanium layer is 50-100 nanometers; the thickness of the second gold layer is at least 300 nanometers.
Citation Information
Cited By
Multi-wavelength quantum cascade laser driven by segmented voltage
CN121076583A
